The Multisoliton Solutions for the (2+1)-Dimensional Sawada-Kotera Equation - Zhenhui Xu; Hanlin Chen; Wei Chen (Abstract and Applied Analysis)
Applying bilinear form and extended three-wavetype of ansätz approach on the (2+1)-dimensional Sawada-Kotera equation, we obtain new multisoliton solutions, including the double periodic-type three-wave solutions, the breather two-soliton solutions, the double breather soliton solutions, and the three-solitary solutions. These results show that the high-dimensional nonlinear evolution equation has rich dynamical behavior.